Lessons Learned through the Muslim Youngsters’ Creative Process of Digital Storytelling (DST) on Peace - Dewi - Puspitasari; Christine Ishii; Mutammam Mutammam; Ahmad Afroni; Reza Adinul Akbar (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
The heterogeneous, rich and unique social cultural background of Indonesiahas routinely become a hidden agenda of hate speech, intolerance, cultural conflicts, and group friction leading to disharmony. Educational intervention is believely needed to address the issue of tolerance. This article aims to investigate ten young students’ experiences with their narration during the creative process of peace-themed Digital Storytelling (DST). By employing a narrative research paradigm, the study reveals the students’ thoughts during the creative DST process. The students’ statements, picture selection, and syntax served as the primary data. Applying Braun and Clark’s thematic analysis, the parameters of peaceful literacy included the commitment to one nation, tolerance, non-violence, and acceptance of various cultures and traditions. The results of this study on the students’ narratives indicated that these young people were peaceful literary agents who use their voices to speak about the importance of upholding cultural traditions, and respecting and accepting others. The study offers a novelty in terms of methods by using a narrative design to narrate the youngsters’ voice related to peace literacy, and in empirical contribution as the supplement to support the national curriculum as well as the implementation of peace-themed peace literacy in educational context.